Age at menarche, ideal cardiovascular health metrics, and risk of diabetes in adulthood: Findings from the REACTION study. Issue 6 (29th December 2020) - Hu, Chunyan; Zhang, Yi; Zhang, Jie; Huo, Yanan; Wan, Qin; Li, Mian; Qi, Hongyan; Du, Rui; Zhu, Yuanyue; Qin, Yingfen; Hu, Ruying; Shi, Lixin; et al.
Abstract: Background: Age at menarche was reported to be associated with the risk of diabetes. However, the impact of ideal cardiovascular health metrics (ICVHMs) on the association between age at menarche and adulthood diabetes risk was unclear. Methods: We included 121 431 women from the nationwide, population‐based cohort of the REACTION study (Risk Evaluation of Cancers in Chinese Diabetic Individuals: a Longitudinal Study). The diagnosis of diabetes was based on the oral glucose tolerance test (OGTT) and glycosylated hemoglobin (HbA1c) measurement. Logistic regression and multiplicative interaction analysis were conducted to investigate the potential interaction effect between age at menarche and ICVHMs on the development of diabetes. Results: The multivariable‐adjusted odds ratios of diabetes across categories of age at menarche (<14, 14‐17, and > 17 years) were 1.22 (95% confidence interval [CI]: 1.17, 1.28), 1.00 (reference), and 0.89 (95% CI: 0.85, 0.93), respectively. In subgroup analysis, significant interactions were detected between total cholesterol/blood pressure levels and age at menarche regarding the risk of diabetes ( P for interaction = .0091 and .0019, respectively). The increased risk associated with age at menarche <14 years was observed in participants with three or fewer ICVHMs, but not in women with four or more ICVHMs ( P for interaction = .0001). Conclusions: Age at menarche was inversely associated with the risk of diabetes in adulthood in Chinese women, and it appeared to be modified by the presence of ICVHMs. Further studies are needed to clarify the precise interrelationship and the generalizability of our results. Abstract : Highlights Results from previous studies on the association of age at menarche and the risk of diabetes in adulthood were inconsistent, and the impact of ideal cardiovascular health metrics (ICVHMs) on this association was unclear. This study showed that early age at menarche was associated with an increased risk of diabetes in middle‐aged and elderly Chinese women, but not in women with ≥4 ICVHMs. There was a significant interaction between the number of ICVHMs and the age at menarche in modifying the risk of diabetes. 摘要: 背景: 既往研究提示月经初潮年龄与糖尿病风险有关。然而尚不清楚理想的心血管健康指标对月经初潮年龄与成年后糖尿病风险之间关系的影响。 方法: 我们纳入全国多中心REACTION研究(中国2型糖尿病患者恶性肿瘤发生风险的流行病学研究)中121431名女性。糖尿病的诊断基于口服葡萄糖耐量试验和糖化血红蛋白测值。使用Logistic回归和乘法项交互作用分析理想的心血管健康指标在月经初潮年龄与糖尿病相关性之间的潜在交互作用。 结果: 多变量校正后; 与月经初潮年龄14‐17岁者相比; 月经初潮年龄<14岁和> 17岁组的糖尿病风险比值比(95%可信区间)分别为1.22(1.17‐1.28)和0.89(0.85‐0.93)。分层分析中; 在总胆固醇; 血压水平和月经初潮年龄与糖尿病风险之间存在显著的交互作用(交互作用P 值分别为 0.0091和0.0019)。在有≤3个理想的心血管健康指标的女性中观察到月经初潮年龄<14岁与成年后糖尿病发生风险增加显著相关; 但在有4个或更多理想的心血管健康指标的女性中则没有观察到显著的风险增加(理想的心血管健康指标的数量与月经初潮年龄之间的交互作用P值 = 0.0001)。 结论: 女性成年后患糖尿病的风险与月经初潮年龄呈负相关; 而这种关系或可因理想的心血管健康指标而改变。需进一步研究以阐明其中的相互关系以及研究结果的普遍性。